We know that reciprocal Fibonacci constant $$\sum_{n=1}^{\infty} \frac{1}{F_n} = \frac{1}{1} + \frac{1}{1} + \frac{1}{2} + \frac{1}{3} + \frac{1}{5} + \frac{1}{8} + \frac{1}{13} + \frac{1}{21} + \cdots \approx 3.3598856662 \dots .$$

Evaluate: $$\sum_{n=1}^{\infty} \frac{(-1)^{n-1}}{F_n} $$


1 Answer 1


I got to say after spending some time with this problem: that's a truly remarkable series, I would love if other people could look into this problem. This is not a full answer, this was just my way to approach the question and I couldn't find some "nice and short" closed-form of the series. Let's begin!

Notice how the series can be split up into an odd and an even part:

$$\sum_{n=1}^{\infty} \frac{(-1)^{n-1}}{F_n} = \sum_{n=0}^{\infty} \frac{1}{F_{2n+1}}-\sum_{n=1}^{\infty}\frac{1}{F_{2n}}$$

Let's first evaluate the series $\sum_{n=0}^{\infty} \frac{1}{F_{2n}}$ because I feel like that's easier a little bit easier.

Evaluating $\sum_{n=0}^{\infty} \frac{1}{F_{2n}}$

This is quite a tricky process, but let's try to work it through. Let $\phi$ denote the golden ratio.

\begin{align} \sum_{n=1}^{\infty} \frac{1}{F_{2n}} &= \sqrt{5}\sum_{n=1}^\infty \frac{\phi^{2n}}{\phi^{4n}-1} \\\\ & = \sqrt{5}\sum_{n=1}^{\infty}\frac{1}{\phi^{2n}-1}-\frac{1}{\phi^{4n}-1} \\\\ & = \sqrt{5}\left(\sum_{n=1}^{\infty}\frac{1}{\phi^{2n}-1}-\sum_{n=1}^{\infty}\frac{1}{\phi^{4n}-1}\right)\end{align}

The sums take form of what's known as a Lambert series. A Lambert series is defined as:

$$F(x)=\sum_{n=1}^\infty a_n\frac{x^n}{1-x^n} $$

Now let the case when $a_n = 1$ be denoted by $L(x)$:

$$L(x) = \sum_{n=1}^\infty \frac{x^n}{1-x^n} = \sum_{n=1}^\infty \frac{1}{x^{-n}-1}$$

And so in the case above we have:

$$\sum_{n=1}^{\infty} \frac{1}{F_{2n}} = \sqrt{5}\left(L(\phi^{-2})-L(\phi^{-4})\right)$$

Now, it is known (and I don't know how; I can't prove it...) that:

$$L(x) = \frac{\psi_x(1)+\ln(1-x)}{\ln(x)}$$

Here $\psi_x(1)$ denotes the q-Polygamma function. Using the identity above we get:

$$\sqrt{5}\left(L(\phi^{-2})-L(\phi^{-4})\right) = \frac{\sqrt{5}}{8\ln(\phi)}\left(\ln(5)+2\psi_{\phi^{-4}}(1)-4\psi_{\phi^{-2}}(1)\right)$$

This as far as I can go. Thus we have arrived at the result that:

$$\sum_{n=1}^{\infty} \frac{1}{F_{2n}} = \frac{\sqrt{5}}{8\ln(\phi)}\left(\ln(5)+2\psi_{\phi^{-4}}(1)-4\psi_{\phi^{-2}}(1)\right)$$

Now according to WolframMathWorld:

$$\frac{\sqrt{5}}{8\ln(\phi)}\left(\ln(5)+2\psi_{\phi^{-4}}(1)-4\psi_{\phi^{-2}}(1)\right) = \frac{\sqrt{5}}{4\ln(\phi)}\left(\psi_{\phi^2}\left(1-\frac{i\pi}{2\ln(\phi)}\right)-\psi_{\phi^2}(1)+i\pi\right)$$

But I have know idea, how they got there. Anyways, the value equals approximately $1.5353705...$

Evaluating $\sum_{n=0}^{\infty} \frac{1}{F_{2n+1}}$

This derivation is pretty much the same as the previous one; you express the Fibonacci numbers in terms of the golden ratio and the simplify it into a Lambert series and then express it in terms of the q-Polygamma function. I did part of this derivation independently, but found that all of these are found at WolframMathWorld. You'll end up with a similar expression to the sum of even Fibonacci numbers:

$$\sum_{n=0}^{\infty} \frac{1}{F_{2n+1}} = -\frac{\sqrt{5}}{4\ln(\phi)}\left(\pi-i\left(\psi_{\phi^2}\left(\frac{1}{2}-\frac{i\pi}{4\ln(\phi)}\right)-\psi_{\phi^2}\left(\frac{1}{2}+\frac{i\pi}{4\ln(\phi)}\right)\right)\right) \tag{1}$$

According to WolframMathWorld an identity (I have no idea how to prove this) is that:

$$\left(\pi-i\left(\psi_{\phi^2}\left(\frac{1}{2}-\frac{i\pi}{4\ln(\phi)}\right)-\psi_{\phi^2}\left(\frac{1}{2}+\frac{i\pi}{4\ln(\phi)}\right)\right)\right) = -(\ln\phi)\vartheta_2^2(\phi^{-2})$$

where $\vartheta_2(q)$ is an Jacobi theta function (read more here). So using this identity on equation $(1)$ we get:

$$-\frac{\sqrt{5}}{4\ln(\phi)}\left(\pi-i\left(\psi_{\phi^2}\left(\frac{1}{2}-\frac{i\pi}{4\ln(\phi)}-\psi_{\phi^2}(\frac{1}{2}+\frac{i\pi}{4\ln(\phi)}\right)\right)\right) = \frac{\sqrt{5}}{4}\vartheta_2^2(\phi^{-2})$$

Which is quite a big simplification if you ask me.

Puting everything together

Recall that: $$\sum_{n=1}^{\infty} \frac{(-1)^{n-1}}{F_n} = \sum_{n=0}^{\infty} \frac{1}{F_{2n+1}}-\sum_{n=1}^{\infty}\frac{1}{F_{2n}}$$

Using the results we have established we get:

$$\sum_{n=1}^{\infty} \frac{(-1)^{n-1}}{F_n} = -\frac{\sqrt{5}}{4\ln(\phi)}\left(\pi-i\left(\psi_{\phi^2}(\frac{1}{2}-\frac{i\pi}{4\ln(\phi)}-\psi_{\phi^2}(\frac{1}{2}+\frac{i\pi}{4\ln(\phi)}\right)\right) - \frac{\sqrt{5}}{4\ln(\phi)}\left(\psi_{\phi^2}\left(1-\frac{i\pi}{2\ln(\phi)}\right)-\psi_{\phi^2}(1)+i\pi\right)$$

\begin{align} &= -\frac{\sqrt{5}}{4\ln(\phi)} \left(\pi-i\left(\psi_{\phi^2}\left(\frac{1}{2}-\frac{i\pi}{4\ln(\phi)}\right)-\psi_{\phi^2}\left(\frac{1}{2}+\frac{i\pi}{4\ln(\phi)}\right)\right) + \psi_{\phi^2}\left(1-\frac{i\pi}{2\ln(\phi)}\right)-\psi_{\phi^2}(1)+i\pi\right)\end{align}

Now let:

$$\Omega = \frac{i\pi}{4\ln(\phi)}$$

Therefore we get:

\begin{align} \sum_{n=1}^{\infty} \frac{(-1)^{n-1}}{F_n} &= -\frac{\sqrt{5}}{4\ln(\phi)} \left(\pi-i\left(\psi_{\phi^2}\left(\frac{1}{2}-\Omega\right)-\psi_{\phi^2}\left(\frac{1}{2}+\Omega\right)\right) + \psi_{\phi^2}\left(1-2\Omega\right)-\psi_{\phi^2}(1)+i\pi\right)\end{align}

That's pretty horrible looking, but I don't know how to simplify it :(

Also note that if you want the series in terms of the Reciprocal Fibonacci Constant $\psi$,

$$\sum_{n=1}^{\infty} \frac{(-1)^{n-1}}{F_n} = \sqrt{\psi^2-4F}$$

where $F$ is:

$$F = \left(\sum_{n=0}^{\infty} \frac{1}{F_{2n+1}}\right)\left(\sum_{n=1}^{\infty}\frac{1}{F_{2n}}\right)$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.